Penghapusan Hak Waris Anak Durhaka: Studi Kasus di Desa Tanjung Mulia - Nasution, Fikri Haikal Fadly; Irwan (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The phenomenon of parents revoking their children's inheritance rights is still found in society, even though Islamic inheritance law has clearly defined the share of each heir. A case that occurred in Tanjung Mulia Village, South Labuhan Batu Regency, shows that a father unilaterally revoked his son's inheritance rights because of the son's behavior as a drug addict. This action raises a dilemma between the moral will of the parents and the binding provisions of Sharia law. The purpose of this study is to analyze the factors behind the revocation of inheritance rights and to examine the views of the Indonesian Ulema Council (MUI) of South Labuhan Batu Regency on this case. This study uses a qualitative method with an empirical juridical approach through in-depth interviews with family members, community leaders, village officials, and the local MUI. The results of the study show that the revocation of inheritance rights is motivated by emotional, moral, and economic factors, as well as the community's misunderstanding of Islamic inheritance law. The MUI emphasizes that the revocation of a child's inheritance rights is not valid according to Sharia law, unless there are clear Sharia reasons such as religious differences or the murder of the heir. Revoking a child's inheritance rights has no valid basis because it contradicts the provisions of the Qur'an Surah An-Nisa verses 11-14, which clearly stipulate the inheritance share of each heir and cannot be changed by individual will.